AIM2 Inhibits BRAF-Mutant Colorectal Cancer Growth in a Caspase-1-Dependent Manner - Shah, Shailendra; Qin, Shaolan; Luo, Yang; Huang, Yizhou; Jing, Ran; Shah, Jay N.; Chen, Jianjun; Chen, Huimin; Zhong, Ming (Frontiers in Cell and Developmental Biology, 2021)
Absent in melanoma 2 (AIM2), a DNA sensor that plays an important role in natural immunity system, has been reported to participate in colorectal cancer (CRC) initiation and development. However, the functional role of AIM2 in BRAF-mutant CRC remains unclear. In this study, we firstly investigated AIM2 expression level in BRAF-mutant CRC tumor tissues. Over-expression of AIM2 in CRC cells was performed to investigate the effect of AIM2 on CRC cell viability, and cell death detection and caspase activity assay were performed to explore the mechanism that AIM2 impacts the growth of BRAF-mutant CRC cells. Moreover, we confirmed the antitumor effect of AIM2 in BRAF-mutant CRC cell-derived tumor xenograft (CDX) models as well as patients-derived organoids (PDOs). Herein, we reported that AIM2 expression was remarkably decreased in BRAF-mutant CRC tumor tissues. Restoring the expression of AIM2 in BRAF mutant CRC cells remarkably inhibits the tumor cell growth by inducing necrotic cell death. Besides, we revealed the mechanism of AIM2-induced cell death is not associated with the activation of DNA-PK/Akt or PTEN, but is in a caspase-1-dependent manner. We also found that over-expression of AIM2 significantly inhibits tumor growth and metastasis in BRAF-mutant CRC in vivo. Moreover, the antitumor effect of AIM2 was further confirmed in BRAF-mutant CRC PDOs. Taken together, our data suggest that AIM2 inhibits BRAF-mutant colon cancer growth in a caspase-1-dependent manner, which may provide evidence to understand the pathogenesis of CRC with BRAF mutant as well as new strategies for manipulation of CRC.